Ethnopharmacological, phytochemistry, and antiviral activity of plants belonging to genus Sida - a systematic review - Zunita Puspita Sari; Achmad Fuad Hafid; Zainul Amiruddin Zakaria; Tutik Sri Wahyuni (Walailak University, 2025)
Viral infections are significant global health concerns, particularly in regions with limited healthcare infrastructure. The leading causes of viral-related mortality worldwide include influenza, COVID-19, Human Immunodeficiency Virus (HIV)/Acquired Immune Deficiency Syndrome (AIDS), and lower respiratory infections, such as pneumonia. Current antiviral therapies, such as protease and reverse transcriptase inhibitors, are effective but limited by high costs, side effects and drug resistance. This review aimed to provide an overview of the current landscape of viral infections, their impact, and available treatments. This review explores the antiviral potential of natural products, focusing on the genus Sida. A systematic literature search using database like PubMed, Science direct, Google Scholar and Wiley Online Library identified on Sida traditional uses, chemical composition and antiviral properties. This review outlined the the overview of Sida Genus as a promising source for new antiviral coumpounds due to its bioactive properties that may inhibit viral infection.